2016
DOI: 10.1080/17435390.2016.1214762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulmonary surfactant on the dissolution, stability and uptake of zinc oxide nanowires by human respiratory epithelial cells

Abstract: Inhaled nanoparticles have high deposition rates in the alveolar region of the lung but the effects of pulmonary surfactant (PS) on nanoparticle bioreactivity are unclear. Here, the impact of PS on the stability and dissolution of ZnO nanowires (ZnONWs) was investigated, and linked with their bioreactivity in vitro with human alveolar epithelial type 1-like cells (TT1). Pre-incubation of ZnONWs with Curosurf® (a natural porcine PS) decreased their dissolution at acidic pH, through the formation of a phospholip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…As our studies are performed on the short‐term exposure (24 h) of cells to NPs, this does not resemble the in vivo situation, where upon peritumoral administration of the NPs, the cancer cells will be exposed to the NPs for longer time periods. The 24 h exposure time has been chosen in line with literature, where cellular NP exposure is often 24 h, mainly driven by the fact that for efficient cellular NP uptake, cells should have undergone one cell cycle . As for different cell types, the cell cycle duration can differ quite a bit, a time period of 24 h is chosen as a mean value.…”
Section: Resultsmentioning
confidence: 99%
“…As our studies are performed on the short‐term exposure (24 h) of cells to NPs, this does not resemble the in vivo situation, where upon peritumoral administration of the NPs, the cancer cells will be exposed to the NPs for longer time periods. The 24 h exposure time has been chosen in line with literature, where cellular NP exposure is often 24 h, mainly driven by the fact that for efficient cellular NP uptake, cells should have undergone one cell cycle . As for different cell types, the cell cycle duration can differ quite a bit, a time period of 24 h is chosen as a mean value.…”
Section: Resultsmentioning
confidence: 99%
“…For example, corona layer was found to impair nanoparticle adhesion onto cell surface or to decrease particle uptake by macrophages [16,28,29]. On the other hand, some studies reported an improved cell internalization [14,30,31,32]. Therefore, the implications of corona layer on AM targeting using inhalable carriers remain still an open issue that needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…5e and f, pre-incubation with Infasurf remarkably reduced MCN-induced toxicity, as reflected by elevated cell viability and improved cellular morphology relative to treated cells without surfactant pre-incubation (p < 0.05). It indicates that the pulmonary surfactant corona formed on the surface of MCNs effectively reduced cytotoxicity of this nanomaterial, similar to the effect of surfactant made on silver nanoparticles (Sweeney et al, 2016;Theodorou et al, 2016).…”
Section: L-mcns Induced More Cytotoxicity Than I-mcns and S-mcnsmentioning
confidence: 57%